Effectiveness of baricitinib in acquired reactive perforating collagenosis: a case report - Zheng, Jianfeng; Ding, Yangfeng; Chen, Yuanyuan; Shi, Yuling; Gao, Yunlu (Frontiers in Immunology, 2024)
Background: Acquired reactive perforating collagenosis (ARPC) poses a clinical challenge with an unclear pathogenesis. This disease frequently proves resistant to immunosuppressive treatments, significantly affecting the quality of life for patients. In our report, we highlight the efficacy of baricitinib as a viable option for maintenance therapy in ARPC. Case Summary: An 81-year-old female presented to our hospital with recurrent pruritus and cup-like ulcerated lesions on her trunk and limbs persisting for one year. She exhibited limited response to oral antihistamines and topical steroids. Past medical history revealed a prolonged history of coronary heart disease and type 2 diabetes spanning several years to decades. Histopathological examination revealed cup-shaped depressions filled with necrotic inflammatory debris. In the dermis, a mixed inflammatory infiltrate comprised of lymphocytes and histiocytes was observed. Van Gieson staining indicated the elimination of fibrous tissue extending from the dermis into the epidermis. Consequently, a diagnosis of ARPC was established. Due to the inadequate response to conventional treatments and severe itching, we initiated baricitinib therapy for ARPC, resulting in gradual symptom improvement. Follow-up assessments showed no adverse reactions and normal laboratory findings. Conclusion: The case report suggests that baricitinib may offer significant therapeutic benefits for ARPC.